Service quality index as customer satisfaction indicator for continous student enrolment at private school in Indonesia - Ngatiyono (2024)
Private schools offering educational services often face criticism for their substandard quality. This study focuses on customer satisfactions where there are academic institutions especially private schools have underestimated their customer satisfaction (i.e. students and parents). Up to this date, there is lack of study on quantitative measure method for measuring customer satisfaction for services at Private schools. As private organization, it is important to have continuous student enrolment for long term survival in education industry. Therefore, this study aims to provide an index as indicator of service quality at private school that reflects student enrolment resulted from customer satisfaction. In this regard, this study applies both approaches; quantitative and qualitative. For the first objective, a systematic literature review was used in order to identify the critical components of service quality in the aspect of customer satisfaction. In the second objective, the model of Service Quality Index (SQI) was developed based on five critical components that determined as (i) Reliability, (ii) Responsiveness, (iii) Tangible, (iv) Warranty, and (v) Empathy. The formula for SQI has been developed based on combination of the five critical components. The SQI measure was developed by derivation of the equations determined for each critical component. In this regard, the critical components and its equation, and the SQI equation have been verified by five experts of education sector in Indonesia. Validation of SQI equation was done through case studies at five private schools in Indonesia by comparing the result of each critical component with annual student enrolment of these schools. Result of the validation proved that only Responsiveness and Warranty has correlation with annual student enrolment. In this regard, Responsiveness and Warranty has been referred as SQI equal to sum of Res-l and Warr-I. In this regard, Responsiveness and Warranty has been referred as the key component for SQI. Therefore, it is important for private school to sustain its responsiveness index and warranty Index in order to have continuous student enrolment. Hence, the SQI can be determined by the sum of Responsiveness Index (Res-1) and Warranty Index (Warr-1). This concludes that continuous student enrolment at private school relies on its responsiveness and warranty on the provided services. However, the initial equation for SQI that consist of five critical components can be further study at other private services such as university, hospital, etc.